Acupuncture for Crohn's disease: a protocol for systematic review and meta-analysis. Issue 3 (15th March 2023) - Han, Qiang; Liu, Daming; Zhang, Peng
Abstract : Introduction: Crohn's disease (CD) is a chronic inflammatory bowel disease that seriously affects the quality of life. While conventional medicines are of limitations, acupuncture has been shown to be a promising therapy. While no systematic review related has been published, the present study aimed to evaluate the efficacy and safety of acupuncture for CD. Methods and analysis: PubMed, the Cochrane Central Register of Controlled Trials and Chinese electronic databases, including China National Knowledge Infrastructure, Wan Fang database, VIP, SinoMed and the Chinese Clinical Trial Registry, will be searched from the establishment of the database until 31 December 2022. Randomised controlled trials evaluating the efficacy and safety of acupuncture/electroacupuncture on patients with CD, controlled by conventional therapies, were included. Outcomes include induction of clinical remission and response, maintenance of remission, and the incidence of adverse events. All articles will be screened and extracted by two reviewers independently. The risk of bias will be evaluated using the revised Cochrane Risk of Bias 2 tool. A fixed effect model or a random effects model will be used based on the assessment of heterogeneity. A subgroup analysis and sensitivity analysis will be carried out if necessary. Publication bias will be analysed, and the strength of the body of evidence for primary outcomes will be graded. Ethics and dissemination: There is no necessity for this study to acquire ethical approval, and this review will be disseminated in a peer-reviewed journal or conference presentation. Trial registration number: CRD42022356967.